TRANSFORMASI PROGRAMMING TV DI ERA DIGITAL: MENYELARASKAN KONTEN DENGAN KEBIASAAN MENONTON MULTIPLATFORM - Edison, Edison; Ahmad, Latifah putri (Jurnal Ilmu Komunikasi, 2025)
The transformation from analog to digital media has fundamentally changed the broadcasting industry, especially television. Audiences are no longer bound to linear broadcast schedules; instead, they prefer to watch their favorite programs flexibly across various digital platforms. This situation requires television stations to adapt their programming strategies to remain relevant amid shifting audience behaviors. This study aims to explore how television adapts in the digital era by tailoring content for viewers who consume media across multiple platforms. Using a qualitative approach through literature review and industry data analysis, the results indicate that the shift toward on-demand and interactive content consumption necessitates innovative, data-driven, and audience-responsive programming strategies. The digitalization of broadcasting and the adoption of new technologies present both challenges and opportunities for local television to survive in the competitive digital media landscape. This study highlights the importance of developing relevant content, adaptive distribution strategies, and leveraging technology to personalize the viewing experience.Transformasi media dari analog ke digital telah mengubah secara mendasar industri penyiaran, khususnya televisi. Kini, penonton tidak lagi terikat pada jadwal siaran linier, melainkan lebih memilih menonton program favorit secara fleksibel melalui berbagai platform digital. Kondisi ini menuntut stasiun televisi untuk menyesuaikan strategi programming agar tetap relevan di tengah perubahan perilaku audiens. Penelitian ini bertujuan mengungkap bagaimana televisi beradaptasi di era digital dengan menyesuaikan konten untuk audiens yang menonton lintas platform. Dengan menggunakan metode kualitatif melalui studi literatur dan data industri, hasil penelitian menunjukkan bahwa pergeseran konsumsi ke konten on-demand dan interaktif mendorong perlunya strategi programming yang inovatif, berbasis data, dan responsif terhadap tren audiens. Digitalisasi penyiaran serta adopsi teknologi baru menjadi tantangan sekaligus peluang bagi televisi lokal untuk bertahan di tengah persaingan media digital. Studi ini menegaskan pentingnya pengembangan konten yang relevan, distribusi adaptif, serta pemanfaatan teknologi untuk personalisasi pengalaman menonton.